1981
DOI: 10.1136/gut.22.6.462
|View full text |Cite
|
Sign up to set email alerts
|

Restorative proctocolectomy with ileal reservoir: a pathophysiological assessment.

Abstract: SUMMARY A metabolic and physiological assessment was carried out in 14 patients who had undergone restorative proctocolectomy with ileal reservoir more than six months previously. The haemoglobin was normal in all but one and plasma electrolytes and serum albumin, calcium, phosphorus, and red cell folate estimations were normal in all. Five patients had low serum iron levels of whom one had an iron deficiency anaemia. The 24 hour faecal fat output was normal in all patients and there was no case of vitamin B12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(55 citation statements)
references
References 13 publications
1
53
1
Order By: Relevance
“…Transformation to a glandular morphology resembling colonic mucosa is common [7]. Histochemical changes in pouch mucin from sialo to sulphomucin are seen in pouches with villous atrophy [5].…”
Section: Discussionmentioning
confidence: 99%
“…Transformation to a glandular morphology resembling colonic mucosa is common [7]. Histochemical changes in pouch mucin from sialo to sulphomucin are seen in pouches with villous atrophy [5].…”
Section: Discussionmentioning
confidence: 99%
“…This process is characterised by histological and histochemical changes, such as severe villous atrophy accompanied by pronounced crypt hyperplasia and elongation [2][3][4][5][6][7]. Histochemical studies using mucin staining have shown a change from small intestinal sialomucin to colorectal-type sulfomucin [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Because histopathological studies in patients with IPAA have demonstrated the transformation of ileal pouch mucosa into colonic mucosa [2][3][4][5] and chemical studies have shown a change of pouch mucin from small bowel-type sialomucin to colorectal sulfomucin [6,7], a theory of colonic transformation of the ileal pouch mucosa has been developed. As a result of the post-operative adaptation of the ileum to its function as neorectum, deep clefts in the ileal pouch mucosa resembling rectal valves may occasionally be observed during fluoroscopic contrast examination (pouchography).…”
mentioning
confidence: 99%
“…Pouchitis is currently being defined with a clinical, endoscopic and histologic scoring system (PDAI) as the disease activity index of more than 7. The incidence of pouchitis is reported as 7% to more than half of the patients whom undergo IPAA operation [2,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%